Medical microbiology and infection at a glance - Gillespie, Stephen H.; Bamford, Kathleen B. (At a glance series, 2012)
This textbook encapsulates the essential principles of modern clinical medical microbiology. It examines the diagnostic path, from the infecting agent through the clinical disease to diagnosis and patient management